नावा ऐलखा पतब् - (:unkn) unknown (Adibasi Socio-Educational & Caltural Association Kumrasole Dumuria, 2001)
The book is a Mathematic text book written in Olchiki script.
A New Mathamatics in Olchiki
Keywords: Santali; Mathematics; Santali; Santali